The linguistic turn, literary theory and historical theory (Historia, 2021)
This essay deals with the relationship between literary theory on the one hand and historical tehory (or philosophy of history) on the other. Since the publication of White's seminal Metahistory in 1973 an orientation on literary theory was recommended to historical theorists. And it is true that this conception of the nature and the tasks of historical theory has given us a wholly new kind of history of historical writing. This has been a great gain we should never allow to be given up again. The orientation on literary theory has, however, not deepened our insights in the relationship between the historical text and the past itself. A careful analysis of what the so-called linguistic turn should mean for historical theory can explain why it is as easy as dangerous to overstate the significance of literary theory for historical theory. The implication is that we should address again the old semantic and epistemological questions with regard to the nature of historical writing.
Keywords: Literary theory; History; Historiography; Linguistic turns; Historical theory